Analisis Undang-Undang Republik Indonesia Nomor 10 Tahun 2009 Tentang Kepariwisataan Terkait Pengembangan Pariwisata Di Kota Medan - Lilik Lilik (Iuris Studia: Jurnal Kajian Hukum, 2021)
Indonesia is an archipelagic country that has a very beautiful landscape, a gem between continents and oceans. Indonesia's strategic geographical location provides many benefits for Indonesia in economic growth, trade routes are wide open for countries passing through Indonesia. The economy grows along with increasing national income and has a significant impact on the community. The economy is a measure of the prosperity of a growing country. One of the pillars of the Indonesian economy is the tourism sector, with beautiful nature and attractive cities. Indonesia presents beautiful destinations in the eyes of the world. Indonesia's strategic location makes Indonesia visited by many local and foreign tourists from land, water and air routes. Destinations in Indonesia improve and continue to make improvements, as well as create a certain characteristic/uniqueness that can later be sold and enjoyed by tourists. Many varieties and kinds are offered in fixing this, areas that have good landscapes will focus on natural tourism areas that have a history of the city due to colonial times and empires in the past will focus on regional city tourism which has many worship centers will focus on tourism. Regional religions that have a variety of types of food on offer will focus on culinary tourism. This type of research is empirical juridical research. Legal regulations governing the development of tourism in the city of Medan. tourism development carried out by the Medan City Tourism Office. Legal regulations governing tourism are Law Number 10 of 2009 concerning Tourism. Regulation of the Minister of Tourism of the Republic of Indonesia Number 10 of 2018 concerning Electronically Integrated Business Licensing Services for the Tourism Sector. Legal policies related to tourism in the development of Medan city tourism based on Law no. 10 of 2009 concerning tourism. The legal policy by the government in developing tourism is the Minister of Tourism Regulation Number 10/2018 concerning electronically integrated business services for the tourism sector. The Medan Mayor's circular regarding the temporary closure of holiday and recreation businesses on religious holidays such as Ramadan, Eid al-Fitr, Eid al-Adha and Christmas in this case the Medan City government publishes it annually. Factors constraint in the development of tourism in the city of Medan Tourism development carried out by the Medan City Tourism Office, already has several tourism objects that are in accordance with the principles being treated. However, Medan City's own regional revenue (PAD) continues to increase because it is supported by the tourism sector's contribution in the form of hotel taxes, restaurant taxes, and entertainment taxes.